Pengaruh Influencer Marketing dan Online Customer Review terhadap Minat Beli Produk Skintific pada Mahasiswa Universitas Nusa Cendana Kupang - Tuan, Stefani Inge I; Kurniawati, Merlyn; Aman, Dominikus K.T; Salean, Debryana Y. (Lembaga Yasin AlSys, 2025)
This study aims to determine the influence of Influencer Marketing and Online Customer Reviews on the Purchase Intention of Skintific products among students of Nusa Cendana University in Kupang. The research is motivated by the development of digital technology, which has increased the role of influencers and customer reviews in skincare product marketing. The method used is a quantitative approach through the distribution of questionnaires to 100 respondents, with data analysis techniques using multiple linear regression. The results show that Influencer Marketing has a positive and significant effect on Purchase Intention of Skintific products, while Online Customer Reviews do not have a significant effect on Purchase Intention. Simultaneously, Influencer Marketing and Online Customer Reviews have a significant effect on Purchase Intention. These findings highlight the importance of influencers in shaping consumer purchase intention, whereas customer reviews alone are not strong enough to influence purchasing decisions. The implications of this study suggest that companies should focus more on effective influencer-based marketing strategies.